In situ decoration of Cd0.05Mn0.05Zn0.90 (ZIF-8) photocatalyst for solar-driven hydrogen production - Kshirsagar S.D.; Shelake S.P.; Islam H.; Bhattacharyya S.; Ahmadipour M.; Sesha Sainath A.V.; Pal U. (Elsevier Ltd, 2025)
In this study, we decorate the Cd0.05Mn0.05Zn0.90-ZIF-8 photocatalyst by partial exchange of Mn2+ and Cd2? with Zn2? metal ions within imidazole frameworks through facile in situ synthesis process at room temperature, which markedly enhances photocatalytic hydrogen generation (PHG). The morphological features exhibited a well-defined truncated rhombic dodecahedron shape. The CMZ8-2 exhibited a superior hydrogen production rate of 3.30 mmolg?1h?1 with an AQY of 8.16%, which is 6 times higher than that of pristine Z8 under simulated full arc solar spectrum at pH 11. Furthermore, the physicochemical insights were established by UV?vis, XRD, HRTEM and binding information by XPS and FTIR studies. Notably, high surface areas (1965.68?1791.61 m2g-1), an impressive average photoexcited charge lifetime of 1.47?1.60 ns, and high transient photocurrent further augmented the PHG performances. The stability of the CMZ8-2 was investigated through photocatalytic cyclic stability test, demonstrating a regeneration efficiency of 93.84% in the fourth cycle. ? 2024 Hydrogen Energy Publications LLC